2015
DOI: 10.1504/ijehv.2015.071639
|View full text |Cite
|
Sign up to set email alerts
|

Participation of an electric vehicle fleet to primary frequency control in France

Abstract: Using electric vehicles (EV) as distributed storage units could be a solution to take advantage of the good availability of EVs and reduce their total cost of ownership. The scientific literature features frequency control as one of the most profitable electric market for EV fleets. This paper presents an economic evaluation of the expected remuneration for a fleet of EVs participating to primary frequency control in France in 2020. First, the modeling of a French EV fleet is addressed. Simulations of the part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…It is a trade off between the implementation complexity and the possible revenue. The starting hypothesis of this work is that it is possible to earn more with V2G than with a unidirectional EV [7]. Assessing by which factor it is more lucrative, is important for the EV owner and for the original equipment manufacturer (OEM).…”
Section: Introductionmentioning
confidence: 99%
“…It is a trade off between the implementation complexity and the possible revenue. The starting hypothesis of this work is that it is possible to earn more with V2G than with a unidirectional EV [7]. Assessing by which factor it is more lucrative, is important for the EV owner and for the original equipment manufacturer (OEM).…”
Section: Introductionmentioning
confidence: 99%
“…In European countries, frequency regulation using EV fleets have been studied in [7] and [8]. The authors in [7] develop an economic evaluation for an EV fleet participating in the French frequency regulation market, exploring regulation strategies for both unidirectional and bidirectional (V2G) power exchanges.…”
Section: Introductionmentioning
confidence: 99%
“…The authors in [7] develop an economic evaluation for an EV fleet participating in the French frequency regulation market, exploring regulation strategies for both unidirectional and bidirectional (V2G) power exchanges. Meanwhile, in [8] an analysis of frequency regulation services via V2G within a micro-grid environment is carried out in Macedonia.…”
Section: Introductionmentioning
confidence: 99%
“…In [10] the authors perform economic analysis of EVs participating in frequency regulation markets, and in [11], certain strategies for the participation of EVs in frequency regulation markets are proposed. EV Frequency regulation markets in France and UK are explored in [12] and [13], respectively. Another study performed on the German market concluded that EVs' profit for participating in frequency regulation markets highly depends on the market conditions [14].…”
Section: Introductionmentioning
confidence: 99%